(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Myocardial ischemia is a frequent complication of diabetes mellitus and is strongly associated with impaired angiogenesis. This study aims to evaluate the morphological features of angiogenesis in the myocardium under experimental diabetes conditions. Experimental models of diabetes, including streptozotocin-induced and alloxan-induced rodents, as well as genetically diabetic models (db/db and ZDF rats), were analyzed. Morphological changes were assessed using histological staining, immunohistochemistry for angiogenesis markers (VEGF, CD31, vWF), electron microscopy, and molecular assays (Western blot, RT-PCR). The results demonstrated a significant reduction in capillary density, downregulation of VEGF and HIF-1α expression, endothelial dysfunction, and ultrastructural alterations of cardiomyocytes and endothelial cells. Suppression of the PI3K/Akt pathway was identified as a key mechanism underlying impaired angiogenesis. These findings highlight the morphological basis of angiogenic impairment in diabetic myocardium and may serve as a foundation for novel therapeutic strategies targeting ischemic heart disease in diabetes.